PERFORMANCE OF SPRING WHEAT AND BARLEY CULTIVARS SOWN IN THE FALL AND SPRING IN NORTHERN ALBERTA - BRIGGS, K. G.; FARIS, D. G. (Canadian Journal of Plant Science, 1973)
Two spring barley (Hordeum vulgare L. emend Lam.) and three spring wheat (Triticum aestivum L.) cultivars were grown over a 2-yr period at three locations in Alberta north of latitude 53°N, to compare the effect of fall and spring seeding on yield and maturity. The cultivars were Olli and Jubilee barley, and Park, Thatcher, and Pitic 62 wheat. The locations were Edmonton, Beaverlodge, and Fort Vermilion. With few exceptions, fall seeding resulted in loss of yield compared with spring seeding, and the fall-seeded materials were no earlier maturing than the comparable spring-seeded materials. For the cultivars and locations studied, fall seeding of spring barley and wheat cannot be recommended. Two spring seeding dates were also compared, the first being considerably earlier than typical commercial seeding at the same location. There were few significant differences in yield between the two spring dates, but the later date considerably delayed the maturity of all cultivars.